1998
DOI: 10.1038/sj.ijo.0800648
|View full text |Cite
|
Sign up to set email alerts
|

Short term response of circulating leptin to feeding and fasting in man: influence of circadian cycle

Abstract: OBJECTIVE: To investigate whether acute feeding induces changes in circulating leptin levels in humans and whether these changes vary according to nycthemeral cycle. METHODS: First experiment. Eighteen male subjects were given a fatty meal at 08.00 h. Blood sampling was performed for 10 h following this meal. Second experiment. Thirteen male subjects were given either a mixed meal or remained fasting either at night (starting at 01.00 h) or during the day (starting at 13.00 h). Blood samples were drawn every h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
2
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 22 publications
8
58
2
2
Order By: Relevance
“…An intact hypothalamic-pituitary axis is therefore not essential for the regulation of leptin circadian rhythm. Other groups reported that the diurnal rhythm of leptin is entrained to meal timing and not to the circadian clock (21,37). Our results show that the pattern of food intake affects the diurnal rhythm but does not agree with a complete lack of effect of the circadian clock, as leptin response to the evening meal was higher.…”
Section: A Elimam and C Marcuscontrasting
confidence: 95%
“…An intact hypothalamic-pituitary axis is therefore not essential for the regulation of leptin circadian rhythm. Other groups reported that the diurnal rhythm of leptin is entrained to meal timing and not to the circadian clock (21,37). Our results show that the pattern of food intake affects the diurnal rhythm but does not agree with a complete lack of effect of the circadian clock, as leptin response to the evening meal was higher.…”
Section: A Elimam and C Marcuscontrasting
confidence: 95%
“…Clapham et al (1997) reported no change in leptin concentrations in either adipose tissue or the plasma for 3 h following a mixed meal. Similarly, Dallongeville et al (1998) reported no change up until 6 h following a mixed meal. The results of the present study confirm these findings and would indicate that, in healthy subjects, circulating leptin concentrations are not altered acutely on feeding.…”
Section: Discussionmentioning
confidence: 97%
“…Circulating catecholamine concentrations are also increased after carbohydrate-rich meals in parallel with serum leptin concentrations, 21,45,46 and a positive association has been found between the elevated circulating leptin and catecholamine concentrations after a carbohydrate-rich diet. 21 Food intake, and predominantly carbohydrate intake, stimulates leptin secretion, 10,12,13,15,21,22 but no association has been found between the increased serum leptin concentrations and the heightened postprandial satiety in the short term (up to 9 h postprandially) in lean or postobese individuals. 21,22 In the context of weight management for obesity, physical activity or exercise alone are better linked with weight maintenance than with enhanced weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] These studies found no relationship between circulating leptin concentrations and appetite sensations acutely after a meal in normal weight or obese individuals 16,17 or during 20 min food exposure in obese individuals. 18 Serum leptin was found to correlate with appetite sensations only during weight loss or maintenance induced by diet and exercise in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation